Acceptance of electric passenger cars in commercial fleets. (October 2018) - Globisch, Joachim; Dütschke, Elisabeth; Schleich, Joachim
Abstract: This paper explores the antecedents of the acceptance of electric vehicles (EVs) in commercial pool car fleets. Conceptually, the analysis draws on the technology acceptance model (TAM). To test the model, structural equation modelling is employed, relying on unique survey-based data of actual users of electric vehicles (N = 575), i.e. from early adopter organisations. In general, the empirical findings support the model. In particular, variables at the organisational level (perceived organisational usefulness) and the organisation memberś reactions to the introduction of EVs (subjective norms) are found to be highly important in supporting the acquisition of EVs in commercial pool car fleets. With regard to the perception of vehicle characteristics, environmental benefits and perceived ease of use are identified as relevant antecedents to EV acceptance (support for acquiring EVs). Unlike the results from the literature that concern private households and company car users, we found a very low effect of the evaluation of the vehicles' driving range.